Efforts To Improve Employee Performance Through Quality Of Work-Life And Effectively Moderated Teamwork Communication On Pt. Rajawali Property Mandiri Medan - Refinda deschamp sembiring; Muhammad Fauzan Azhmy; Ezzah Nahrisah; Teguh Setiawan; Pitono (Publisher Cv. Inara, 2022)
This study aims to determine the effect of quality of work-life and teamwork on the performance of employees of PT Rajawali Properti Mandiri Medan. To find out whether the effectiveness of communication moderates the effect of quality of work-life and teamwork on employee performance at PT Rajawali Properti Mandiri Medan. The total population in this study amounted to 116 people, and by using a saturated sampling technique, a sample of 116 people was obtained. The analysis technique used is multiple linear regression and residual MRA technique. The results showed that the quality of work-life had a significant effect on the performance of the employees of PT Rajawali Properti Mandiri Medan. Teamwork affects employee performance at PT Rajawali Properti Mandiri Medan. The effectiveness of communication proved significant in moderating the quality of work-life on employee performance and the effectiveness of communication proved significant in moderating teamwork on employee performance.